Phytopharmacovigilance in the Elderly: Highlights from the Brazilian Amazon - Sousa Lima, Carolina Miranda de; Teles Fujishima, Mayara Amoras; Franca dos Santos, Braulio Erison; Lima, Bruno de Paula; Mastroianni, Patricia Carvalho [UNESP]; Oliveira de Sousa, Francisco Fabio; Silva, Jocivania Oliveira da (Hindawi Ltd, 2019)
Practices described as traditional medicine may coexist with formalized, science-based medicine. In this context, the present study aimed to verify the profile of the elderly who consumed herbal medicines concomitantly with medications and to identify suspected adverse drug reactions (ADRs) in the Brazilian Amazon (Macapa, Amapa). The study was carried out in two steps: a cross-sectional study (structured questionnaire) and a clinical study (pharmacotherapeutic follow-up). Out of 208 participants, 78.8% were female with age between 60 and 69 years (58.7%), 59.1% used herbal medicines concurrently with medications, and 40.9% did not report use of herbal medicine. Losartan was the most used medication, and Lippia alba (Mill.) N.E. Br was the most common herbal medicine used. The total prevalence of suspected ADRs, among the elderly who answered the structured questionnaire, was 41.3%, with 27.4% being in the elderly who used herbal medicines and medications, and 13.9% being in the elderly who used only medications. Meanwhile, the total prevalence of suspected ADRs was 71.0% among the elderly patients who underwent pharmacotherapeutic follow-up, 60.5% in elderly who used herbal medicines and medications, and 10.5% in elderly who used only medications. The most reported ADR symptoms were related to disorders that affect the nervous system (38.4%) in the structured questionnaire and related to digestive disorders (36.4%) in the pharmacotherapeutic follow-up. The probability associated with the occurrence of a given ADR in the face of a set of demographic, socioeconomic, and clinical variables was estimated; the results showed that, in the studied population, only sex (p = 0.030) had an influence on the occurrence of ADR. The prevalence of ADRs with probable causality was high in this study population, but it was only sex-related, although more prevalent in the elderly who consume herbal medicines.